Comprehensive Analyses of the Immunological and Prognostic Roles of an IQGAP3AR/let-7c-5p/IQGAP3 Axis in Different Types of Human Cancer - Yuan, Yixiao; Jiang, Xiulin; Tang, Lin; Yang, Hong; Wang, Juan; Zhang, Dahang; Duan, Lincan (Frontiers in Molecular Biosciences, 2022)
Accumulating evidence has indicated that IQGAP3 plays crucial roles in the diverse cancer progression, but there is no study focus on the prognostic, upstream regulation mechanism and immunological roles of IQGAP3 in pan-cancer. In this study, we found that IQGAP3 was elevated in human pan-cancer, and high expression of IQGAP3 was correlated with tumor stage, lymph node metastasis and poor prognosis in diverse human cancer. The DNA methylation of IQGAP3 was highly negative with the expression of IQGAP3 in diverse cancer, high DNA methylation was related to better OS in human cancer. High IQGAP3 mRNA expression was associated with TMB, MSI, immune cell infiltration and immune modulators. KEGG pathway enrichment analyses showed that IQGAP3 was involved in the cell cycle. We also found that IQGAP3 expression was associated with the diverse drug sensitivity in cancer cells lines. Finally, we found that PTBP1 and IQGAP3AR/let-7c-5p axis were potential regulation the expression of IQGAP3, respectively. IQGAP3AR was highly expression in diverse cancer and correlated with unfavorable prognosis of pan-cancer. However, the let-7c-5p expression were decreased in different cancer, high expression of let-7c-5p was correlated with good prognosis in pan-cancer. Finally, we perform qPCR and IHC assays shown that IQGAP3 was highly expression in NSCLC cell lines and cancer tissue. In this study, we provided the first evidence show that IQGAP3AR/let-7c-5p/IQGAP3 axis plays indispensable roles in the cancer progression and immune response in human pan-cancer.